ChemInform Abstract: Reusable Directing Groups [8‐Aminoquinoline, Picolinamide, Sulfoximine] in C(sp3)—H Bond Activation: Present and Future. Issue 31 (August 2015) - Rit, Raja K.; Yadav, M. Ramu; Ghosh, Koushik; Sahoo, Akhila K.
Abstract Review: [47 refs.